ANALYSIS OF THE PROSPECTS FOR DEVELOPMENT OF CERTAIN ASPECTS OF LICENSING IN THE FIELD OF FIRE SAFETY - Sergey S. Voevoda; Irina F. Zenkova (Актуальные вопросы пожарной безопасности, 2021)
The article considers the possibility of amending the licensing requirements regarding the confirmation of the qualifications of permanent employees who are the license applicants (licensees). Fulfillment of the specified requirements is mandatory if it is intended to carry out (implement) fire fighting activities in settlements, at industrial facilities and infrastructure facilities, as well as activities for installation, maintenance and repair of fire safety facilities for buildings and structures. The analysis of regulations on licensing of fire safety activities, approved by the resolutions of the Government of the Russian Federation is carried out. These regulations are implemented as part of realization of “regulatory guillotine”. Furthermore, the general mechanism for formation of the system for independent qualification assessment, including in the field of fire safety is analyzed as well as the prospects for amending licensing requirements were considered. The above mentioned analysis is carried out using the provisions of regulatory legal acts of the Russian Federation and regulatory documents. It is concluded that the nature of predictable changes should correspond to the general direction of development of the unified National qualification system. The article also considers the current state of formation stages of professional standards in the field of fire safety. The development of such standards is assigned to the Council for professional qualifications in the field of safety in emergency situations.